Peran Literasi Keuangan Digital dalam Mendukung Profitabilitas Pedagang di Surabaya - Dwi Arief Rahman; DMuhammad Yasin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
The development of digital financial technology has accelerated the transition from cash-based to cashless payment systems across various economic sectors, including traditional markets. One of the most widely adopted innovations is the Quick Response Code Indonesian Standard (QRIS), which offers convenience, speed, and security in financial transactions. This study aims to analyze the role of digital financial literacy in supporting the utilization of QRIS and its implications for the profitability and business sustainability of traditional market traders in Surabaya. The study employed a descriptive qualitative approach, with data collected through observation and documentation of traders' transaction activities. The findings indicate that the utilization of QRIS among traditional market traders remains suboptimal. This condition is influenced by limited digital financial literacy, insufficient technological skills, and the readiness of business owners to adopt digital payment systems. In addition, concerns regarding transaction security and limited technological competence, particularly among elderly traders, remain significant barriers to digital transformation. Nevertheless, digital financial literacy has been shown to improve transaction efficiency, facilitate financial record-keeping, reduce transaction errors, and support more effective business management. Therefore, strengthening digital financial literacy is a strategic factor in optimizing QRIS adoption to enhance profitability and ensure the long-term sustainability of traditional market businesses in the digital economy.